Medical Management in Stonefish Envenomation in Bushehr Port - Mahboobeh Jafari; Gholam Hossein Mohebbi; Amir Vazirizadeh; Iraj Nabipour (Iranian South Medical Journal, 2014)
Background: The Persian Gulf is one of the best places to find tropical venomous animals. The second cause of marine injuries in the Persian Gulf region is stonefish, it seems that the medical practitioners in this region are not familiar with the medical management of stonefish envenomationon. Materials and methods: A total of 16 patients with stonefish envenomation were serially examined in emergency rooms of academic hospitals of Boushehr port and Delvar clinic. In these patients local and systemic manifestations, first aid management and therapeutic interventions were evaluated. Results: The most common sites of injury were lower extremity (14 cases) and upper extremities (2 cases). The most common prescribing medication for relief of pain was injection of local lidocaine. The second and third most common prescribed drugs were parenteral antihistamines and corticosteroids, respectively. Hot water was not used in any of patients. Only in 2 cases antibiotic were given, whereas tetabolin was not prescribed in any of them. Conclusion: Although the most effective pain relieving intervention for stonefish envenomation, it was not used in injured patients in the current study. Likewise, tetabolin was not used. The medical practitioners should be encouraged to use immersion of the injured site in hot water, injection of local lidocaine without adrenalin, tetabolin injection and prophylactic broad spectrum antibiotics in stonefish envenomation.